PREVALENCE AND MANAGEMENT STRATEGIES OF PRIMARY AMENORRHEA AT A TERTIARY LEVEL HOSPITAL OF PAKISTAN - Sidra Javaid; Sahira Agha; Kanwal Atif; Tahmina Mahar; Sabahat Fatima; Azra (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Aim: This study aimed to determine the frequency, causes, and management strategies of primary amenorrhea in a tertiary care hospital in Pakistan.Place and Duration: This study was conducted at PNS Hafeez Islamabad from March 2024 to March 2025Methods: The study included patients meeting the criteria for primary amenorrhea, excluding those with secondary amenorrhea. Data collection involved detailed medical history, physical examinations assessing height, weight, BMI, nutritional status, and secondary sexual characteristics. Pelvic or rectal examinations evaluated external genitalia and uterine presence. Diagnostic tests, including complete blood count, hormonal assays, karyotyping, and pelvic ultrasonography (transabdominal or transvaginal), were tailored to initial findings. Laparoscopy was performed when indicated, and pregnancy tests ruled out related causes.Results: Among 878 patients with amenorrhea, 28 were diagnosed with primary amenorrhea (0.29% prevalence). Patients aged 14-22 years, with 14.3% married, underwent karyotyping (92.9%), hormonal assays (53.6%), and laparoscopy (35.7%). Müllerian anomalies were the most common cause (42.9%), followed by premature ovarian failure (28.6%), hypothalamic disorders (14.3%), polycystic ovary syndrome (7.1%), and constitutional delayed puberty (7.1%). Treatments included hormonal therapy for hypoestrogenic states, surgical corrections for anatomical defects, and lifestyle modifications for hypothalamic causes.Conclusion: Primary amenorrhea, though rare, requires comprehensive evaluation and tailored management. Multicenter studies are needed to explore genetic predispositions and optimize long-term outcomes.